The Role of Moderation in The Company's Age on Financial Slack's Relationship to Company Performance - Ceicilia Bintang Hari Yudhanti; Herlina Yoka Roida (Jurnal Ilmu Manajemen & Ekonomika, 2022)
This study examines whether financial slack is associated with firm performance and whether this relation-ship is moderated by firm size and firm age. This study consists of 251 firm-years covering the period from 2017to 2019 of 85 companies in the manufacturing industry listed on the Indonesia Stock Exchange (IDX). Our findings indicate that financial slack has a negative effect on company performance. This negative ef-fect is weakened if the size of the company is larger and the age of the company is more mature. In addi-tion, companies with financial slack tend not to use the slack of company financial resources for the benefit of the company. This can be attributed to the tendency of the company's management to use these re-sources to increase additional income or remuneration for managers. The management considers the com-pany's short-term performance which has an impact on increasing management's welfare. These findings emphasize that big size companies will compete with younger companies that tend to invest in research and development. Therefore, large companies will use financial slack for the benefit of the company in or-der to maintain the company's survival in the future. Mature companies have experience in managing com-pany resources and competence in gaining access to the resources needed to survive or grow. Therefore, based on experience and journey to gain access to funding, financial slack will be used for the benefit of the company. This study supports the prediction with evidence from Indonesia manufacture companies, and conclude that financial slack will be managed in aim maintain access to funding in the future.